Karakteristik Fisiko-Kimia dan Sensori Bakso Ikan Parang-parang (Chirocentrus dorab) dengan Substitusi Tepung Buah Pedada (Sonneratia caseolaris) - Mutiara Pertiwi; Herpandi Herpandi; Rodiana Nopianti (Jurnal FishtecH, 2018)
The purpose of this research was to know the physicochemical and sensory characteristic of wolf herring's fishballs with flour crabapple mangrove (Sonneratia caseolaris) substitution. The research was conducted from February until May 2017. This research used randomized block design with 5 treatments and was repeated 2 times as the group. The substitution treatments were 0%, 25%, 50%, 75% and 100% of flour apple crab mangrove. The parameters of this research were chemical analysis such as water content, ash content, protein content, lipid content and carbohydrate content. The physical analysis was texture (firmness), and sensory analysis was color, taste, aroma, visible, texture, teeth cutting test, and folding test. The results showed that treatment gave a significant effect on water content, ash content, and protein content. In the physical analysis, the results treatment gave significant effect on texture (firmness) and sensory analysis also a significant effect on visible, color, taste, texture, and folding test. The water content of wolf herring's fish balls 72.61%-79.60%, ash 1.91%-3.50%, protein 6.63%-16.57%, lipid 0.24%-0.38%, and carbohydrate 8.51%-10.01%. The texture (firmness) of this fishballs was 58.80gf-115.60gf. The visible sensory were 5.0-6.12, color 4.96-6.08, aroma 4.96-5.76, taste 4.60-5.64, texture 4.72-5.96, teeth cutting test 5.72-6.56, and folding test 2.84-4.0. Substitution of flour crabapple mangrove 75% and 100% able to make wolf herring's fishballs meet the requirements quality standards of moisture content, ash content, protein content, and fat content for fishball products.